The impact of social media celebrity endorsement on Malaysian university students' consumption behavior - Thong, Bao Chye (2023)
According to several past research, celebrity endorsement consistently draws positive responses from buyers to advertisements. Aziz et al. (2019) and Ahmad et al. (2019) previous studies have studied the influence of celebrity endorsement on consumer buying behaviour. However, there is a lack of in-depth studies on the purchasing behaviour of Malaysian University students. Therefore, this study uses the Source Attractiveness and Credibility Model to focus on celebrity endorsement's impact on Malaysian University consumption behaviour. In addition, this study will utilize quantitative research, including an online questionnaire form disseminated to University students. A sample size of 150 University students will be targeted as the respondents. The obtained data were analysed using SPSS, and the results show celebrity attractiveness and expertise significantly impact Malaysian University students' consumption behaviour. However, celebrity trustworthiness is unrelated to Malaysian University students' consumption behaviour. The future study suggested being conducted in a qualitative method to enrich researchers' understanding of the respondents' opinions. The researcher also suggested comparing the impact of celebrity endorsement in a wide range of ages and focusing on specific product categories.